Intake ground vortex characteristics - Mishra, N.; MacManus, David G.; Murphy, J. P. (Sage, 2011)
The development of ground vortices when an intake operates in close proximity to the ground has been studied computationally for several configurations including front and rear quarter approaching flows as well as tailwind arrangements. The investigations have been conducted at model scale using a generic intake geometry. Reynolds Averaged Navier–Stokes calculations have been used and an initial validation of the computational model has been carried out against experimental data. The computational method has subsequently been applied to configurations that are difficult to test experimentally by including tailwind and rear quarter flows. The results, along with those from a previous compatible study of headwind and pure cross-wind configurations, have been used to assess the ground vortex behaviour under a broad range of velocity ratios and approaching wind angles. The characteristics provide insights on the influence of the size and strength of ground vortices on the overall quality of the flow ingested by the intake.
Keywords: intake; ground vortex; RANS; headwind; cross-wind; tailwind; distortion